Overview on Cryptosporidium bovis and Its Effect on Calves in Some Governorates in Egypt - Amer R. Abdelaziz; Amin Tahoun; Hanem El-Sharkawy; Moustafa M. Abd El-Salam; Mohammed Alorabi; Ahmed M. El-Shehawi; Rasha A. El Meghanawy; Essam E Toukhy; Ahmed M. Abd El-Salam; Shimaa S. G. Sorour (Journal of Tropical Medicine)
The present study was conducted to elucidate the prevalence of Cryptosporidium bovis in suckling and weaned cattle calves (Bubalus bubalis) from different governorates in northern, middle, and southern Egypt, such as Behera, Menofia, Qaliubiya, Assiut, and Sohag; result revealed that from the overall examined fecal samples (n = 825), the overall prevalence was 7.27%, the highest significant infection rate was in young suckling calves less than one month (8.2%), and seasonally, winter season has the highest significant level (11.24%), but sex and locality were of no significant effect on the prevalence of infection in this study. Gene sequencing and phylogenetic analysis of the 18SSU-rRNA gene of the local bovine isolate were performed, and it was found that C. bovis genotype was highly similar to human isolate, which provoke the zoonotic transmission of bovine isolate to humans and identified as a potential source for human cryptosporidiosis infection in Egypt.